Frontiers in Staphylococcus aureus - Enany, Shymaa; Crotty Alexander, Laura E. (IntechOpen, 2017)
Staphylococcus was first recognized as a human pathogen in 1880 and was named for its grape cluster-like appearance. In 1884, Staphylococcus aureus was identified and named for its vibrant golden color, which was later found to be the result of golden toxin production. Here, experts examine in-depth patterns of S. aureus colonization and exposures in humans, mammals, and birds that have led to the development of various clinical diseases. The mode of transmission of S. aureus and different methods for its detection in different samples are defined. Conventional antibiotic options to treat this aggressive, multifaceted, and readily adaptable pathogen are becoming limited. Alternative, novel chemotherapeutics to target S. aureus are discussed in the pages within, including herbal medicines, bee products, and modes of delivery.